ASSOCIATION BETWEEN PERSONALITY TRAITS AND SMOKING CIGARETTE AMONG CRITICAL CARE NURSES: ACROSS-SECTIONAL STUDY - Asad , Mohanad Jamal; Majeed, Haider Mohammed (Journal of Forensic Medicine and Toxicology, 2024)
Background: Personality traits are related to cigarette smoking. However, little is known about the link between smoking and change in personality. Therefore, the present study examined whether current cigarette smoking is associated with personality change among nurses. Methodology: This cross-sectional study was conducted on 200 nurses working at Baquba Teaching Hospital and Baladrooz general hospital in Diyala Governorate, from September15, 2023 to January10, 2024. A non-probability purposive sample technique was utilizing in current study, the personality traits assessment toward smoking were assessed using the personality assessment questionnaire (PAQ). The data were analysed using Statistical Package for Social Science (SPSS) version 26. Descriptive statistics were used in this study (e.g., mean, standard deviation, frequency, and percentage). For quantitative data Pearson correlation, and the Chisquare test was employed to determine the degree and direction of the relationship between the smoking cigarrete and personality traits among nursing. Results: There were 200 participants whose mean age (± SD) of 28.97 (±6.695) years old. Moreover, 69.5% of the participants were aged 20 to 29 years old. 95 % were men and reminder were women, 57 % had diploma education, more than half of the respondents (65.5%) were smoke cigarettes, while 84% of them smoking electronic cigarettes, and 60.5% smoke hookah. Related the number of years of smoking high percentage of nursing67%, it reached duration of smoking between 1 and 5 years. More than twothirds of nurses had a moderate-level personality trait. There was significant difference in years of nursing experience the distribution between groups at a P- value <0.05.While there was no statistically significant relationship with the variables (age groups, and educational level). Conclusion: The nurses surveyed in this study showed that there is high significant correlation between personality trait and type of smoking. We recommend awareness campaigns related preventive measures and policies to increase the awareness about the adverse health effects of smoking and to further counteract its global epidemic should necessarily target smoking-induced mental health risks.